Peningkatan Motivasi dan Hasil Belajar Fisika Kompetensi Usaha, Energi dan Daya Melalui Pembelajaran dengan Pendekatan Saintifik Siswa SMK - Wahyono Wahyono (Radiasi : Jurnal Berkala Pendidikan Fisika, 2020)
This research aims to improve the motivation and results of learning physics effort competency, energy, and power through learning with a scientific approach for students of grade X TKRO 4 SMK Negeri 2 Wonosobo. The data collection techniques used documentation and observation techniques to process the data of observation instruments. The results showed that based on theorists through study with scientific approaches can improve the motivation of learning physics for students. Based on empirical (research), the internal motivation aspect rises by 3.48% and the external motivation aspect rises by 3.01%. Then through learning with scientific approaches can increase the motivation to learn the physics effort competence in energy and power subject matter. Then by theoretical, that through learning with scientific approaches can improve student learning results. While based on empirical (research), apparently the highest value remains 86.67, the lowest value rises 37.06%, the average value rises 35.14% and the number of students who graduated up 41.67%, then through learning with scientific approaches can improve the results of the study of Physics effort competence, energy, and power for students. Therefore through learning with a scientific approach can improve the motivation and results of the physics learning of effort competence, energy, and power for students in grades X TKRO 4 SMK Negeri 2 Wonosobo Semester 2 years lesson 2019/2020. Findings in this study reinforce theoretical and empirical perspectives, in the teacher's effort to achieve optimal learning results.